The influence of leader behaviour, psychological empowerment, job satisfaction, and organizational commitment on turnover intention - Dhladhla, Thamsanqa John (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm)--University of Stellenbosch, 2011.